Removal mechanism of heavy metal (Cu, Ni, Zn, and Cr) in the presence of cyanide during electrocoagulation using Fe and Al electrodes. (February 2020) - Kim, Taeyeon; Kim, Tae-Kyoung; Zoh, Kyung-Duk
Graphical abstract: Highlights: Electrocoagulation was applied simultaneously remove four heavy metals. Alkaline pH condition is favored for removing metals during electrocoagulation. Fe electrode showed better metal removal performance compared to Al electrode. The removal of Ni was inhibited the most in the presence of cyanide. The mass of sludge formed and the amount of energy consumed were calculated. Abstract: Heavy metals have frequently been detected in metal plating wastewater. In this study, electrocoagulation method using iron (Fe) and aluminum (Al) electrodes was applied to simultaneously remove four heavy metals (Cu, Ni, Zn, Cr) in artificial metal plating wastewater. The Fe electrode showed greater removal efficiency for especially Cr than did the Al electrode due to the reduction of Cr 6+ ion by Fe 2+ ions produced from electrode. Alkaline pH favored electrocoagulation because of the abundance of hydroxide (OH − ) ions; thus, metal hydroxides can be formed readily under alkaline pH. The metal removal increased with current density, as Fe 2+ ion was generated more effectively at high current. However, the electrolyte concentration did not significantly affect metal removal efficiency. In electrocoagulation experiments using Fe electrodes, the mass of sludge formed was 0.68–2.50 kg/m 3 and the amount of energy consumed was 0.37–2.78 kW h/m 3, respectively, during the treatment of artificial metal plating wastewater containing four heavy metals in the absence of cyanide, which increased to 3.64–4.74 kg/m 3 and 4.80–5.04 kW h/m 3 for artificial wastewater in the presence of cyanide. The FTIR spectra of the sludge samples generated when using Fe and Al electrodes showed that all four metals exhibited OH stretching peaks, implying that main removal mechanism of metals during electrocoagulation is the precipitation with metal hydroxide. Iron sludge was composed mainly of Fe3 O4 and FeO(OH), and Al sludge was mostly AlO(OH). When using Fe electrode in the presence of cyanide, cyanide was also adsorbed onto iron sludge via Fe-CN bonding.